Studi Pendahuluan: Pengaruh Cognitive Transcendence Strategy terhadap Stres dan Adiksi Internet pada Mahasiswa Kedokteran - Aisyah, Ammara; Pasiak, Taufiq Fredrik; Harfiani, Erna; Makkiyah, Feda Anisah (Faculty of Medicine, Universitas Andalas, 2023)
The incidence of Internet addiction in the world continues to increase in various circles of society. One of the causes is stress. Mindfulness methods such as the Cognitive Transcendence Strategy (CTS) are strategies for changing behavior through cognitive functions and spiritual values. Objective: To determined the effect of CTS on stress in medical students who suffer from internet addiction. Methods: This research is a quantitative experimental study with the Quasi Eksperimental Nonequivalent Control Group Design. The sample of 16 people was collected through a purposive sampling technique based on inclusion and exclusion criteria. Data were analyzed using the Wilcoxon test. Results: Univariate shows that 60.1% of medical students experience internet addiction, of which 38.4% is in the mild category, 21.4% were moderate, and 0.4% were severe. The stress level of selected respondents based on the HRV analyzer stress index obtained was 62.5% normal, 12.5% good, 18.75% excellent, and 6.25% poor. The results of the Wilcoxon statistical test between CTS and stress were found to be p = 0.261 (p>0.05), which shows that there is no effect of CTS administration on stress statistically. The results of the Wilcoxon test between CTS and internet addiction showed a p = 0.012 (p<0.05). Conclusion: There is the influence of CTS on internet addiction.Keywords: cognitive transcendence strategy, stress, internet addiction, medical student